Proximity to the Frontier, Markups, and the Response of Innovation to Foreign Competition : Evidence from Matched Production-Innovation Surveys in Chile - Cusolito, Ana Paula (World Bank, Washington, DC, 2021)
This paper employs a matched firm production/innovation panel data set from Chile to explore the response of firm innovation to the increased competition arising from the China shock. In addition to covering a wider range of innovation inputs and outputs than previously possible, the data allow generating measures of markups and efficiency (physical total factor productivity) that correspond more closely to the concepts of rents and technological leadership envisaged in the Schumpeterian literature. Except for the 10 percent most productive plants, increased competition depresses most measures of innovation. Falling rents exacerbate declines among laggards, while rising rents further increase innovation among leaders.